Effects of Lactobacillus plantarum ZG-7 on the intestinal barrier and intestinal flora of Muscovy ducks infected with avian pathogenic Escherichia coli - Peng, Song; Xie, Bilin; Mei, Guiheng; Ma, Yaxiong; Lin, Xin; Zhao, Mengshi; Lin, Fengqiang; Li, Zhaolong (Frontiers in Immunology, 2026)
IntroductionAvian pathogenic Escherichia coli (APEC) poses a serious challenge to global poultry production, where it causes enteritis, septicemia, and high mortality, resulting in substantial economic losses. Although antibiotics have been traditionally used to control APEC, the rise of antimicrobial resistance and concerns over drug residues underscore the need for effective and sustainable alternatives. Probiotics have emerged as promising candidates because of their ability to modulate the intestinal microbiota, strengthen host immunity, and preserve epithelial barrier integrity. In this study, we investigated the protective role of Lactobacillus plantarum ZG-7 against APEC infection in Muscovy ducks.Methods40 one-day-old ducks (equal numbers of males and females) were randomly allocated to five groups (n = 8 per group): control (CON), probiotic alone (LP), APEC-infected (EC), probiotic-pretreated APEC-infected (LPEC), and colistin sulfate-treated APEC-infected (CSEC), with the latter serving as a positive control and exhibiting expected protective effects. On day 7, ducks in the EC and LPEC groups received two oral doses of pathogenic E. coli O78 (3 × 10^9 CFU/mL, 0.2 mL) at an 8-hour interval, while ducks in the CON and LP groups received sterile saline. Serum and intestinal samples were collected on day 15.ResultsAPEC infection significantly reduced average daily gain during days 9–15 and across the trial. Histopathological analysis showed epithelial disruption, crypt and gland loss, reduced goblet cells, diminished mucus secretion, and decreased expression of tight junction proteins (ZO-1, MUC2, Occludin). In contrast, L. plantarum ZG-7 treatment alleviated intestinal injury and restored growth performance. 16S rRNA sequencing further revealed that APEC challenge increased the abundance of unclassified Lachnospiraceae, Lachnoclostridium, norank RF39 group, and Paludicola (P < 0.05), whereas L. plantarum ZG-7 treatment reduced these taxa. Moreover, probiotic supplementation alone significantly enriched Bacteroides (P < 0.001).DiscussionTaken together, these results demonstrate that L. plantarum ZG-7 helps maintain a beneficial microbial composition, protects epithelial barrier function, and mitigates the adverse effects of APEC infection in Muscovy ducks, highlighting its potential as a natural and sustainable alternative for improving poultry health.